QMF Bank Design with Cosh-Hamming Window - Kamislioglu, Bircan; Karaboga, Nurhan (Ieee, 2015)
In this study, QMF (Quadrature Mirror Filter-quarter Mirror Filter) bank is proposed design hybrid windowing function based on Cosh and Hamming the use of the window. The performance of the filter banks are designed in different degrees; pass and stop band attenuation with failure to pre was evaluated taking into consideration. The obtained results of the intended QMF filter bank with Cosh-Hamming window function can be used as bank showed successful design.
Cosh-Hamming Penceresi ile QMF Bankasi Tasarimi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: QMF Bank; Windowing; Cosh Window; Hamming Window